2020
DOI: 10.1021/jacs.0c09684
|View full text |Cite
|
Sign up to set email alerts
|

Strongly Reducing (Diarylamino)benzene-Based Covalent Organic Framework for Metal-Free Visible Light Photocatalytic H2O2 Generation

Abstract: Photocatalytic reduction of molecular oxygen is a promising route toward sustainable production of hydrogen peroxide (H 2 O 2 ). This challenging process requires photoactive semiconductors enabling solar energy driven generation and separation of electrons and holes with high charge transfer kinetics. Covalent organic frameworks (COFs) are an emerging class of photoactive semiconductors, tunable at a molecular level for high charge carrier generation and transfer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
250
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 367 publications
(277 citation statements)
references
References 46 publications
4
250
0
3
Order By: Relevance
“…When the light was switched on, in situ grafted surface >OH groups served as hole traps to produce H + as shown in Eq. (9)- (12). The pH was quickly reduced and reached 4.38 in the spontaneous ACNT-5 system; this pH is even lower than that of the CN system with a sacrificial agent (pH = 5.10) due to lower hydroxyl radical production.…”
Section: The Capture Of H + and The Generation Of H + By The In Situ mentioning
confidence: 88%
See 1 more Smart Citation
“…When the light was switched on, in situ grafted surface >OH groups served as hole traps to produce H + as shown in Eq. (9)- (12). The pH was quickly reduced and reached 4.38 in the spontaneous ACNT-5 system; this pH is even lower than that of the CN system with a sacrificial agent (pH = 5.10) due to lower hydroxyl radical production.…”
Section: The Capture Of H + and The Generation Of H + By The In Situ mentioning
confidence: 88%
“…Semiconductor photocatalytic reduction of O2 in H2O to produce H2O2 provides an alternative and viable approach [9][10][11][12][13]. For example, Teranishi et al utilized a hybrid photocatalyst, Au/TiO2, for H2O2 production [14], while Kim et al used a graphene oxide/CdS hybrid composite to produce H2O2 by harnessing low-energy photons (635 nm) [15].…”
mentioning
confidence: 99%
“…Recently, COFs have emerged as potential candidates for several photocatalytic transformations. [138][139][140][141] Pachfule et al, 138 showed that a crystalline diacetylene functionalized COF performs better than its amorphous counterpart in photocatalytic hydrogen evolution reaction. Hence, it is clear that crystallinity is a crucial component in improving the charge carrier separation and transfer kinetics.…”
Section: Materials Advancesmentioning
confidence: 99%
“…[10] Due to their extensive tailorability and attractiveness for av ast range of applications,t he structural design of MOFs and COFs has formed av ery active field of research. [11][12][13][14][15] Thanks to am eticulous control over synthesis conditions and an ever-expanding versatile set of experimentally available building blocks,i th as even become possible to synthesize combinations of building blocks in different structures.T of ully explore the functionalities of the enormous amount of potential structures that can be formed from agiven set of building blocks,anaccurate protocol is needed to systematically derive structural models for these materials at realistic working conditions of temperature and pressure. [16,17] Such structural characterization is ac onditio sine qua non for the atomically guided design of functional applications in the fields of catalysis,sorption, light harvesting and more.…”
Section: Introductionmentioning
confidence: 99%
“…Within this toolbox lies the concept of reticular design, [8] where judiciously chosen building blocks are assembled in a predesigned topology, giving rise to materials such as metal‐organic frameworks (MOFs) [9] and covalent organic frameworks (COFs) [10] . Due to their extensive tailorability and attractiveness for a vast range of applications, the structural design of MOFs and COFs has formed a very active field of research [11–15] . Thanks to a meticulous control over synthesis conditions and an ever‐expanding versatile set of experimentally available building blocks, it has even become possible to synthesize combinations of building blocks in different structures.…”
Section: Introductionmentioning
confidence: 99%